Tibetan evidence for the sources of chapters of the synoptic Suvarṇa-prabhāsottama-sūtra T 664 ascribed to Paramārtha - Radich, Michael (Buddhist studies review, 2016)
Four chapters survive of a supposed translation of the Suvarna-prabhasottama-sutra by Paramartha (499-569). Versions of these chapters are also found in a later Chinese version of the sutra by Yijing. In earlier work, I have argued that these chapters were most likely composed in China, basing my argument upon extensive verbatim correspondences between these chapters and a number of earlier Chinese texts. However, a significant obstacle still stands in the way of this thesis. A Tibetan version of the sutra (here called 'Tib II') also includes the same chapters, and Tibetan tradition holds that this version is a translation from Sanskrit. Here, I examine evidence that suggests that these portions of Tib II might in fact be translations from Chinese, despite the reports of Tibetan bibliographers. In closing, I consider some broader implications of my findings.
Gesehen am 03.12.2025